Passivated transition metal disulfide nanosheet as well as passivation method and application thereof
By dispersing transition metal dichalcogenide nanosheets in passivation reagents and performing ultrasonic treatment and heating treatment, the problem of insufficient passivation methods in the prior art is solved, and the fluorescence performance and stability of the nanosheets are significantly improved. , achieving efficient and safe passivation effect.
Patent Information
- Application Number
- CN202411549355.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
There is no general passivation method in the prior art that can effectively improve the fluorescence performance of transition metal dichalgenide compound materials, and the material has the disadvantages of poor safety and toxicity.
Passivation is achieved by dispersing transition metal dichalcogen compound nanosheets in passivation reagents, sonication and heating treatment. This method is simple in process and has strong versatility, which can significantly improve the fluorescence performance and stability of nanosheets.
The passivated transition metal dichalcogenide nanosheets obtained through this method have significantly improved the fluorescence performance and good fluorescence stability. The fluorescence intensity of WS2 nanosheets has increased by up to 103 times. The fluorescence stability of MoS2 nanosheets has only decreased by 2.9 within 60 days. %.
Smart Images

Figure CN119432377A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterials, and specifically relates to a photoelectric nanomaterial, and in particular to a passivated transition metal disulfide compound nanosheet and a passivation method and application thereof. Background Art
[0002] Transition metal dichalcogenides (TMDs) have attracted great attention in optoelectronic applications due to their electronic and optical properties, such as direct band gap and chemical and thermal stability. However, the absolute photoluminescence quantum yield (PLQY) of monolayer TMDs prepared by traditional exfoliation or chemical synthesis is usually less than 1%, and the low photoluminescence (PL) performance limits the application of TMDs materials. Although TMDs have made progress in various optoelectronic applications, there are still many challenges in improving their intrinsic quality and enhancing their PL performance.
[0003] Compared with bulk materials, nanosheets have unique geometric (2D) and quantum (confinement) properties, with size effects and prominent edge effects. TMDs nanosheets have broad application prospects in many application fields, such as field effect crystals, ultrasensitive chemical sensors, and flexible electronics. Generally speaking, in physical applications such as transistors, photodetectors, and electroluminescent devices, nanosheets with high crystallinity and higher PL performance are required. However, due to defects in the material itself, dangling bonds and other factors, energy is dissipated in the form of non-radiative recombination. In addition, heteroatoms and functional groups in the material can also affect the fluorescence stability of the material through charge transfer with the surrounding environment, and even lead to fluorescence quenching. These factors have an adverse effect on the study of nanosheets with higher PL performance.
[0004] CN117534606A introduces carbazole groups and triphenylamine groups into highly luminescent anthracene groups through solid-state topological chemical reactions to construct a stable and orderly stacking structure, which can promote the energy absorption of monomer ground-state electrons through photodimerization of anthracene groups and thus achieve solid-state fluorescence enhancement of organic molecules.
[0005] CN114180543A discloses a method for passivating black phosphorus nanosheets, wherein a DC voltage is applied to black phosphorus as a cathode and platinum as an anode in an electrolyte of tetrabutyl cations and metal ions such as gold to perform electrochemical passivation to obtain passivated black phosphorus nanosheets. The black phosphorus nanosheets have good oxidation resistance and photoelectric responsiveness.
[0006] CN110098331A obtains a surface-passivated CdTe nanocrystal film by depositing a chelating agent and a CdCl2 solution on a CdTe nanocrystal film for thermal passivation, thereby significantly increasing the surface free energy and dangling bonds of the CdTe nanocrystals, generating more active centers, and reducing the carrier recombination rate of CdTe.
[0007] CN118325612A has developed a method for passivating the surface of quantum dots. The passivation method passivates the surface defects of the quantum dots and improves the fluorescence peak intensity of the quantum dots by adding phosphine compounds to cadmium selenide, lead sulfide, and lead selenide quantum dot solutions.
[0008] However, the above materials have the disadvantages of poor safety and toxicity. There is no universal passivation method in the prior art that can improve the fluorescence properties of transition metal dichalcogenide materials. Therefore, there is an urgent need for a universal and stable method to inhibit non-radiative processes and improve the fluorescence properties of transition metal dichalcogenide nanosheets. Summary of the invention
[0009] The purpose of the present invention is to provide a passivated transition metal disulfide compound nanosheet and its passivation method and application. The passivation method provided by the present invention has strong versatility and simple process, and the passivated transition metal disulfide compound nanosheet obtained by the passivation method of the present application has significantly improved fluorescence performance and good fluorescence stability.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] In a first aspect, the present invention provides a method for passivating transition metal dichalcogenide nanosheets, the passivation method comprising the following steps:
[0012] (1) dispersing transition metal dichalcogenide nanosheets in a passivation agent, and subjecting the dispersion to a first ultrasonic treatment to obtain an original dispersion of transition metal dichalcogenide nanosheets;
[0013] (2) heating the original dispersion of the transition metal disulfide compound nanosheets in step (1) to obtain the passivated transition metal disulfide compound nanosheets.
[0014] The present invention uniformly mixes the passivation agent and the transition metal disulfide compound nanosheets by ultrasonic treatment before passivation, which can significantly improve the passivation effect. Through the cavitation effect of the ultrasonic treatment, the transition metal disulfide compound nanosheets can be fully dispersed in the passivation agent. Through the heat treatment, the passivation agent can fully passivate the transition metal disulfide compound nanosheets. In the passivation method of the present invention, the passivation must be carried out under heating conditions, and the heat passivation will significantly improve the fluorescence performance and stability of the transition metal disulfide compound nanosheets.
[0015] Compared with the passivation method in the prior art, the present invention has the advantages of simple process, strong versatility, good fluorescence enhancement effect and strong fluorescence stability. The prepared passivated transition metal disulfide compound nanosheets have good redispersibility and obvious fluorescence enhancement intensity. The fluorescence intensity of WS2 nanosheets is enhanced by up to 103 times, and the fluorescence stability is strong. The fluorescence stability of the passivated transition metal disulfide compound nanosheets only decreases by 2.9% in 60 days.
[0016] Preferably, the transition metal dichalcogenide nanosheets in step (1) include any one of MoS2, MoSe2, WS2, WSe2, Bi2Se3, InS2 or InSe2, or a combination of at least two of them. Typical but non-limiting combinations include MoS2 and MoSe2, MoS2 and WS2, MoS2 and WSe2, MoS2 and Bi2Se3, MoS2 and InS2, MoS2 and InSe2, MoSe2 and WS2, MoSe2 and WSe2, MoSe2 and Bi2Se3, MoSe2 and InS2, MoSe2 and InSe2, WS2 and WSe2, WS2 and Bi2Se3, WS2 and InS2, WS2 and InSe2, WSe2 and Bi2Se3, WSe2 and InS2, WSe2 and InSe2, Bi2Se3 and InS2, Bi2Se3 and InSe2 or InS2 and InSe.
[0017] In the present invention, the lateral size refers to the maximum size of the transition metal dichalcogenide nanosheet in the length or width direction. The appropriate lateral size and thickness of the transition metal dichalcogenide nanosheet will affect the improvement of the fluorescence performance of the final passivated transition metal dichalcogenide nanosheet.
[0018] Preferably, the lateral size of the transition metal dichalcogenide nanosheets in step (1) is less than 100 nm, for example, it can be 1 nm, 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm, preferably 2 nm-10 nm.
[0019] Preferably, the thickness of the transition metal dichalcogenide nanosheet in step (1) is less than 3 nm, for example, it can be 0.6 nm, 0.8 nm, 1 nm, 1.2 nm, 1.4 nm, 1.6 nm, 1.8 nm, 2 nm, 2.2 nm, 2.4 nm, 2.6 nm, 2.8 nm or 3 nm, preferably 0.6 nm-2 nm.
[0020] In the present invention, the lateral size of the transition metal dichalcogenide nanosheet is less than 100 nm, the thickness is less than 3 nm, the passivation effect is better, and it is more conducive to improving the fluorescence performance and fluorescence stability of the transition metal dichalcogenide nanosheet.
[0021] Preferably, the passivation reagent in step (1) comprises one or a combination of at least two of tetrahydrofuran, N-methylpyrrolidone, diethyl ether or diethyl sulfide. Typical but non-limiting combinations include tetrahydrofuran and N-methylpyrrolidone, tetrahydrofuran and diethyl ether, tetrahydrofuran and diethyl sulfide, N-methylpyrrolidone and diethyl ether, N-methylpyrrolidone and diethyl sulfide or diethyl ether and diethyl sulfide, preferably tetrahydrofuran.
[0022] The concentration of the original dispersion of the transition metal disulfide nanosheets of the present invention will affect the final passivation effect and fluorescence performance. A suitable concentration is more conducive to improving the passivation effect and is easy to collect and redisperse.
[0023] Preferably, the mass concentration of the transition metal disulfide nanosheets in the original dispersion of the transition metal disulfide nanosheets in step (1) is 0.005 mg / mL-0.2 mg / mL, for example, it can be 0.005 mg / mL, 0.01 mg / mL, 0.015 mg / mL, 0.02 mg / mL, 0.025 mg / mL, 0.03 mg / mL, 0.035 mg / mL, 0.04 mg / mL, 0.045 mg / mL, 0.05 mg / mL, 0.055 mg / mL, 0.06 mg / mL, 0.065 mg / mL, 0.07 mg / mL, 0.075 mg / mL, 0.08 mg / mL, 0.085 mg / mL, 0.09 mg / mL, 0.095 mg / mL or 0.1 mg / mL, preferably 0.02 mg / mL-0.1 mg / mL.
[0024] The ultrasonic power and time described in the present invention can ensure the passivation degree and fluorescence enhancement intensity of the transition metal dichalcogenide nanosheets during passivation. The greater the ultrasonic power, the shorter the time it takes to evenly disperse the transition metal dichalcogenide nanosheets. The smaller the ultrasonic power, the longer the time required to evenly disperse the transition metal dichalcogenide nanosheets. Both probe-type ultrasound and water bath-type ultrasound can disperse the transition metal dichalcogenide nanosheets.
[0025] Preferably, the power of the first ultrasonic treatment in step (1) is 50 W-800 W, for example, it can be 50 W, 100 W, 120 W, 140 W, 160 W, 180 W, 200 W, 250 W, 300 W, 350 W, 400 W, 450 W, 500 W, 550 W, 600 W, 650 W, 700 W, 750 W or 800 W, preferably 100 W-200 W.
[0026] Preferably, the time for the first ultrasonic treatment in step (1) is 1 min-100 min, for example, it can be 1 min, 5 min, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 95 min or 100 min, preferably 10 min-30 min.
[0027] Preferably, the first ultrasonic treatment in step (1) is probe-type ultrasound or water bath-type ultrasound.
[0028] Preferably, the ultrasonic treatment in step (1) further comprises standing after the first ultrasonic treatment is completed.
[0029] The standing after ultrasonic treatment described in the present invention must be before heating treatment. The standing time needs to select appropriate standing conditions according to the ultrasonic power. If the ultrasonic power is large, the standing time is correspondingly extended. The standing is to ensure that the high temperature state of the local transition metal disulfide nanosheet dispersion caused by ultrasound can naturally return to room temperature.
[0030] Preferably, the standing temperature is 0°C-40°C, for example, it can be 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C or 40°C, preferably 15°C-25°C, preferably 20°C.
[0031] Preferably, the standing time is 0.2h-5h, for example, it can be 0.2h, 0.4h, 0.5h, 0.6h, 0.8h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, preferably 0.2h-1h, preferably 0.5h.
[0032] Preferably, the temperature of the heating treatment in step (2) is 100°C-200°C, for example, it can be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C, preferably 100°C-120°C.
[0033] The temperature of the heating treatment in step (2) of the present invention is adjusted according to the selection of the passivation agent, and the temperature of the heating treatment needs to be greater than the boiling point of the passivation agent.
[0034] Preferably, the heating treatment time in step (2) is 10 min-400 min, for example, it can be 10 min, 50 min, 100 min, 150 min, 200 min, 230 min, 235 min, 240 min, 245 min, 250 min, 300 min, 350 min or 400 min, preferably 230 min-250 min.
[0035] Preferably, after the heating treatment in step (2) is completed, the mixture is allowed to cool to 0°C-40°C, for example, 0°C, 5°C, 15°C, 20°C, 25°C, 30°C, 35°C or 40°C, preferably 25°C.
[0036] Preferably, the cooling time is 10 min-30 min, for example, it can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, preferably 15 min.
[0037] The heating treatment process described in the present invention includes a static cooling process after heating, which is performed after the heating is completed. The static cooling temperature is preferably 0°C-40°C, which is more conducive to improving the fluorescence performance and achieving the technical purpose of the present invention.
[0038] Preferably, the passivation method further comprises a redispersion process after standing and cooling.
[0039] Preferably, the redispersion process comprises dispersing the passivated transition metal disulfide compound nanosheets in a dispersing agent to obtain a passivated transition metal disulfide compound nanosheet dispersion.
[0040] Preferably, the dispersing agent includes any one of N-methylpyrrolidone, N-vinylpyrrolidone, N-cyclohexylpyrrolidone, N-octylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, acetone, ether, diethyl sulfide, methanol, ethanol, toluene, isopropanol or water, or a combination of at least two thereof.
[0041] Preferably, the mass concentration of the passivated transition metal disulfide compound nanosheets in the passivated transition metal disulfide compound nanosheet dispersion is 0.001 mg / mL-10.0 mg / mL, for example, 0.001 mg / mL, 0.005 mg / mL, 0.01 mg / mL, 0.015 mg / mL, 0.02 mg / mL, 0.025 mg / mL, 0.03 mg / mL, 0.035 mg / mL, 0.04 mg / mL, 0.045 mg / mL, 0.05 mg / mL, 0.055 mg / mL, 0.06 mg / mL, 0.065 mg / mL, 0.07 mg / mL, 0.075 mg / mL. / mL, 0.08mg / mL, 0.085mg / mL, 0.09mg / mL, 0.095mg / mL, 0.1mg / mL, 0.5mg / mL, 1mg / mL, 1.5mg / mL, 2mg / mL, 2.5mg / mL, 3mg / mL, 3.5mg / mL, 4mg / mL, 4.5mg / mL, 5mg / mL, 5.5mg / mL, 6mg / mL, 6.5mg / mL, 7mg / mL, 7.5mg / mL, 8mg / mL, 8.5mg / mL, 9mg / mL, 9.5mg / mL or 10mg / mL, preferably 0.02mg / mL-0.1mg / mL.
[0042] Preferably, the dispersing method of the redispersing process comprises a second ultrasonic treatment.
[0043] Preferably, the ultrasonic power of the second ultrasonic treatment is 100W-200W, for example, it can be 100W, 110W, 120W, 130W, 140W, 150W, 160W, 170W, 180W, 190W or 200W, preferably 100W.
[0044] Preferably, the ultrasonic time of the second ultrasonic treatment is 5 min-60 min, for example, it can be 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 55 min or 60 min, preferably 10 min.
[0045] When the ultrasonic power of the present invention is too small, the ultrasonic effect is low, which is not conducive to the dispersion of the passivated transition metal dichalcogenide nanosheets and affects the fluorescence properties of the passivated transition metal dichalcogenide nanosheets. When the ultrasonic power is too large, it has little effect on improving the dispersion effect and fluorescence properties, but will cause energy waste.
[0046] In the present invention, the "first" and "second" in the first ultrasonic treatment and the second ultrasonic treatment are only used to distinguish two different ultrasonic treatment processes, and are not used as any limitation on the corresponding ultrasonic treatment processes.
[0047] The second invention provides a passivated transition metal dichalcogenide nanosheet, wherein the passivated transition metal dichalcogenide nanosheet is obtained by the passivation method described in the first aspect.
[0048] Preferably, the thickness of the passivated transition metal dichalcogenide nanosheet is less than 3 nm, preferably 0.6 nm-2 nm, for example 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2.0 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, 2.9 nm or 3.0 nm, etc.
[0049] Preferably, the lateral size of the passivated transition metal dichalcogenide nanosheet is less than 100 nm, preferably 2-10 nm, for example, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm, etc.
[0050] In a third aspect, the present invention provides a use of the passivated transition metal dichalcogenide nanosheets as described in the second aspect in the preparation of optoelectronic devices, optical films, biosensors, fluorescent indicators and fluorescent conversion materials.
[0051] The numerical range described in the present invention includes not only the point values listed above, but also any point values other than the above numerical values.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The present invention provides a method for passivating transition metal disulfide nanosheets with good versatility, wide application range and simple process. By dispersing the transition metal disulfide nanosheets in a passivation reagent and combining it with heat treatment, passivated transition metal disulfide nanosheets with excellent fluorescence performance and good fluorescence stability are successfully obtained.
[0054] (2) The passivated transition metal disulfide nanosheets prepared by the passivation method of the present invention are effectively passivated, and the fluorescence performance of the passivated transition metal disulfide nanosheets is significantly enhanced. The fluorescence intensity of the passivated WS2 nanosheets is increased by up to 103 times, and the fluorescence stability of the passivated transition metal disulfide nanosheet dispersion in the air is significantly improved. The fluorescence stability of the passivated MoS2 nanosheet dispersion in the air environment can be maintained for 60 days with only a decrease of 2.9%.
[0055] (3) The passivated transition metal disulfide compound nanosheets obtained by the passivation method of the present invention can be widely used in optoelectronic devices, optical films, biosensors, fluorescent indicators and fluorescent conversion materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 Comparison of fluorescence test results of the passivated transition metal dichalcogenide nanosheet dispersion and the original nanosheet dispersion provided in Example 1 of the present invention and Comparative Example 1.
[0057] Figure 2 Comparison of fluorescence test results of the passivated transition metal disulfide compound nanosheet dispersion and the original nanosheet dispersion provided in Example 2 of the present invention and Comparative Example 2.
[0058] Figure 3 Comparison of fluorescence test results of the passivated transition metal disulfide nanosheet dispersion and the original nanosheet dispersion provided in Example 3 of the present invention and Comparative Example 3.
[0059] Figure 4 Comparison of fluorescence test results of the passivated transition metal disulfide compound nanosheet dispersion and the original nanosheet dispersion provided in Example 4 of the present invention and Comparative Example 4.
[0060] Figure 5 Comparison of fluorescence test results of the passivated transition metal dichalcogenide nanosheet dispersion and the original nanosheet dispersion provided in Example 5 of the present invention and Comparative Example 5.
[0061] Figure 6 Comparison of fluorescence test results of the passivated transition metal disulfide nanosheet dispersion and the original nanosheet dispersion provided in Example 6 of the present invention and Comparative Example 6.
[0062] Figure 7Comparison of fluorescence test results of the passivated transition metal dichalcogenide nanosheet dispersion and the original nanosheet dispersion provided in Example 7 of the present invention and Comparative Example 7.
[0063] Figure 8 The fluorescence test results of the passivated transition metal dichalcogenide nanosheet dispersion provided in Example 1 after being placed for 20 days, 40 days and 60 days.
[0064] Fig. 9 The electroluminescent results of the passivated nanosheets provided in Application Example 1 coated as fluorescence conversion materials on a commercial electroluminescent chip.
[0065] Fig.10 The electroluminescence results of the commercial electroluminescent chip coated with the non-passivated nanosheets provided in Application Example 1 are compared with the electroluminescent results of the commercial electroluminescent chip. DETAILED DESCRIPTION
[0066] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0067] Example 1
[0068] This embodiment provides a method for passivating MoS2 nanosheets, and the method specifically comprises the following steps:
[0069] (1) MoS2 nanosheets with a lateral size of 2.2 nm and a thickness of 1.0 nm were dispersed in tetrahydrofuran, ultrasonically dispersed at 120 W for 15 min, and allowed to stand at 20 ° C for 0.5 h to obtain a MoS2 nanosheet original dispersion with a mass concentration of 0.02 mg / mL of MoS2 nanosheets;
[0070] (2) The original dispersion of MoS2 nanosheets was heated at 140°C for 10 min, and then cooled to 25°C for 15 min to obtain passivated MoS2 nanosheets with a lateral size of 2.3 nm and a thickness of 1.2 nm;
[0071] (3) N-methylpyrrolidone dispersant was added to the passivated MoS2 nanosheets, and ultrasonic dispersion was performed at 100 W for 15 min to obtain a passivated MoS2 nanosheet dispersion with a mass concentration of 0.02 mg / mL of the passivated MoS2 nanosheets.
[0072] Example 2
[0073] This embodiment provides a method for passivating MoS2 nanosheets, which is exactly the same as Example 1, except that the lateral size of the MoS2 nanosheets in step (1) is 55.9 nm, and the passivated MoS2 nanosheets with a lateral size of 56.2 nm and a thickness of 1.2 nm are prepared in step (2).
[0074] Example 3
[0075] This embodiment provides a method for passivating MoS2 nanosheets, which is exactly the same as Example 1, except that the lateral size of the MoS2 nanosheets in step (1) is 99.7 nm, and the passivated MoS2 nanosheets with a lateral size of 99.8 nm and a thickness of 1.2 nm are prepared in step (2).
[0076] Example 4
[0077] This embodiment provides a method for passivating WS2 nanosheets, and the method specifically comprises the following steps:
[0078] (1) WS2 nanosheets with a lateral size of 5.9 nm and a thickness of 0.7 nm were dispersed in tetrahydrofuran, ultrasonically dispersed at 100 W for 10 min, and allowed to stand at 25 ° C for 0.2 h to obtain a WS2 nanosheet original dispersion with a mass concentration of 0.06 mg / mL of WS2 nanosheets;
[0079] (2) The original dispersion of WS2 nanosheets was heated at 110°C for 240 min and cooled to 15°C for 25 min to obtain passivated WS2 nanosheets with a lateral size of 6.0 nm and a thickness of 0.8 nm;
[0080] (3) N-methylpyrrolidone dispersant was added to the passivated WS2 nanosheets, and ultrasonic dispersion was performed at 100 W for 10 min to obtain a passivated WS2 nanosheet dispersion with a mass concentration of 0.08 mg / mL of the passivated WS2 nanosheets.
[0081] Example 5
[0082] This embodiment provides a method for passivating MoSe2 nanosheets, and the method specifically comprises the following steps:
[0083] (1) MoSe2 nanosheets with a lateral size of 10 nm and a thickness of 0.8 nm were dispersed in diethyl sulfide, ultrasonically dispersed at 450 W for 100 min, and allowed to stand at 0° C. for 2.5 h to obtain a MoSe2 nanosheet original dispersion with a mass concentration of 0.15 mg / mL;
[0084] (2) The original dispersion of MoSe2 nanosheets was heated at 120°C for 230 min, and then cooled to 0°C for 20 min to obtain passivated MoSe2 nanosheets with a lateral size of 10.5 nm and a thickness of 0.9 nm;
[0085] (3) Dimethyl sulfoxide dispersant was added to the passivated MoSe2 nanosheets, and ultrasonic dispersion was performed at 150 W for 5 min to obtain a passivated MoSe2 nanosheet dispersion with a mass concentration of 0.1 mg / mL of the passivated MoSe2 nanosheets.
[0086] Example 6
[0087] This embodiment provides a method for passivating Bi2Se3 nanosheets, and the method specifically comprises the following steps:
[0088] (1) Bi2Se3 nanosheets with a lateral size of 3.2 nm and a thickness of 2.0 nm were dispersed in ether, ultrasonically dispersed at 200 W for 30 min, and allowed to stand at 40 ° C for 1 h to obtain a Bi2Se3 nanosheet original dispersion with a mass concentration of 0.1 mg / mL of Bi2Se3 nanosheets;
[0089] (2) The original dispersion of Bi2Se3 nanosheets was heated at 100°C for 250 min, and then cooled to 35°C for 10 min to obtain passivated Bi2Se3 nanosheets with a lateral size of 3.4 nm and a thickness of 2.1 nm;
[0090] (3) Tetrahydrofuran dispersant was added to the passivated Bi2Se3 nanosheets, and ultrasonic dispersion was performed at 120 W for 60 min to obtain a passivated Bi2Se3 nanosheet dispersion with a mass concentration of 10 mg / mL.
[0091] Example 7
[0092] This embodiment provides a method for passivating MoS2 nanosheets, and the method specifically comprises the following steps:
[0093] (1) MoS2 nanosheets with a lateral size of 45 nm and a thickness of 2.4 nm were dispersed in N-methylpyrrolidone, ultrasonically dispersed at 800 W for 1 min, and allowed to stand at 15 ° C for 5 h to obtain a MoS2 nanosheet original dispersion with a mass concentration of 0.2 mg / mL of MoS2 nanosheets;
[0094] (2) The original dispersion of MoS2 nanosheets was heated at 200°C for 320 min, and then cooled to 0°C for 30 min to obtain passivated MoS2 nanosheets with a lateral size of 47 nm and a thickness of 2.6 nm;
[0095] (3) Diethyl sulfide dispersant was added to the passivated MoS2 nanosheets, and ultrasonic dispersion was performed at 200 W for 30 min to obtain a passivated MoS2 nanosheet dispersion with a mass concentration of 6 mg / mL.
[0096] Example 8
[0097] This embodiment provides a method for passivating WS2 nanosheets, which is the same as Example 4 except that the lateral size of the WS2 nanosheet in step (1) is 110 nm, and the passivated WS2 nanosheet with a lateral size of 110.7 nm and a thickness of 0.72 nm is obtained through step (2).
[0098] Example 9
[0099] This embodiment provides a method for passivating WS2 nanosheets, which is the same as Example 4 except that the thickness of the WS2 nanosheets in step (1) is 4.5 nm, and the passivated WS2 nanosheets with a lateral size of 6.1 nm and a thickness of 4.7 nm are obtained through step (2).
[0100] Example 10
[0101] This embodiment provides a method for passivating WS2 nanosheets, which is the same as Example 4 except that the mass concentration of WS2 nanosheets in the original dispersion of WS2 nanosheets is 0.002 mg / mL.
[0102] Embodiment 11
[0103] This embodiment provides a method for passivating WS2 nanosheets, which is the same as Example 4 except that the mass concentration of WS2 nanosheets in the original dispersion of WS2 nanosheets is 0.3 mg / mL.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 1 is that MoS2 nanosheets with a lateral size of 2.2 nm and a thickness of 1.0 nm are dispersed in N-methylpyrrolidone dispersant, and ultrasonic dispersion is performed at 100 W for 15 minutes to obtain a MoS2 nanosheet dispersion with a mass concentration of 0.02 mg / mL, that is, the passivation treatment is not performed by the passivation method described in the present invention.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 2 is that MoS2 nanosheets with a lateral size of 55.9 nm and a thickness of 1.0 nm are dispersed in N-methylpyrrolidone dispersant, and ultrasonic dispersion is performed at 100 W for 15 minutes to obtain a MoS2 nanosheet dispersion with a mass concentration of 0.02 mg / mL, that is, the passivation treatment is not performed by the passivation method described in the present invention.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 3 is that MoS2 nanosheets with a lateral size of 99.7 nm and a thickness of 1.0 nm are dispersed in N-methylpyrrolidone dispersant, and ultrasonic dispersion is performed at 100 W for 15 minutes to obtain a MoS2 nanosheet dispersion with a mass concentration of 0.02 mg / mL, that is, the passivation treatment is not performed by the passivation method described in the present invention.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 4 is that WS2 nanosheets with a lateral size of 5.9 nm and a thickness of 0.7 nm are dispersed in N-methylpyrrolidone dispersant, and ultrasonic dispersion is performed at 100 W for 10 min to obtain a WS2 nanosheet dispersion with a mass concentration of 0.08 mg / mL, that is, the passivation treatment is not performed by the passivation method described in the present invention.
[0112] Comparative Example 5
[0113] The difference between this comparative example and Example 5 is that MoSe2 nanosheets with a lateral size of 10 nm and a thickness of 0.8 nm are dispersed in a dimethyl sulfoxide dispersant, and ultrasonic dispersion is performed at 150 W for 5 min to obtain a MoSe2 nanosheet dispersion with a mass concentration of 0.1 mg / mL of MoSe2 nanosheets, that is, the passivation treatment is not performed by the passivation method described in the present invention.
[0114] Comparative Example 6
[0115] The difference between this comparative example and Example 6 is that Bi2Se3 nanosheets with a lateral size of 3.2 nm and a thickness of 2 nm are dispersed in tetrahydrofuran dispersant, and ultrasonic dispersion is performed at 120 W for 60 min to obtain a Bi2Se3 nanosheet dispersion with a mass concentration of 10 mg / mL of Bi2Se3 nanosheets, that is, the passivation treatment is not performed by the passivation method described in the present invention.
[0116] Comparative Example 7
[0117] The difference between this comparative example and Example 7 is that MoS2 nanosheets with a lateral size of 45 nm and a thickness of 2.4 nm are dispersed in diethyl sulfide dispersant, and ultrasonic dispersion is performed at 200 W for 30 minutes to obtain a MoS2 nanosheet dispersion with a mass concentration of 6 mg / mL, that is, the passivation treatment is not performed by the passivation method described in the present invention.
[0118] Application Example 1
[0119] This application example provides a use of a passivated WS2 nanosheet as a fluorescence conversion material, comprising coating the passivated WS2 nanosheet dispersion obtained in Example 4 on a commercial electroluminescent chip, and drying at 40°C for 24 hours to obtain a fluorescence conversion electroluminescent device.
[0120] Comparative application example 1
[0121] This application example provides a use of WS2 nanosheets as a fluorescence conversion material, comprising dispersing WS2 nanosheets with a lateral size of 5.9 nm and a thickness of 0.6 nm that have not been passivated by the passivation method described in the present invention in N-methylpyrrolidone, ultrasonically dispersing at 100 W for 10 minutes to obtain a WS2 nanosheet dispersion with a mass concentration of 0.08 mg / mL, coating the dispersion on a commercial electroluminescent chip, and drying at 40°C for 24 hours to obtain a fluorescence conversion electroluminescent device.
[0122] Fluorescence performance test:
[0123] The above-mentioned original dispersion of transition metal disulfide nanosheets and the passivated dispersion of transition metal disulfide nanosheets were added to a 1×1×3.5 cm quartz cuvette, and the cuvette was placed in the sample pool of the fluorescence spectrometer, and an excitation wavelength of 380 nm was used to excite and collect the emission peak at 400-700 nm. In order to avoid the interference of the solvent Raman peak, a 430 nm filter was added to remove the influence of the Raman peak when testing nanosheets with lateral dimensions of 55.9 nm and 99.7 nm. The test fluorescence spectrometer used in the embodiment of the present invention is HORIBA, and the instrument model is Fluoro Max Plus.
[0124] Fluorescence stability test:
[0125] The method described in this test has the same instrument parameters as the above-mentioned fluorescence performance test, except that the passivated MoS2 nanosheet dispersion obtained in Example 1 is placed at room temperature for 20 days, 40 days and 60 days before being tested.
[0126] Electroluminescence test:
[0127] The original dispersion of transition metal dichalcogenide nanosheets and the passivated dispersion of transition metal dichalcogenide nanosheets are coated on a commercial electroluminescent chip, respectively, the residual solvent is dried at 40°C, and then a digital source meter is used to provide current, the source meter brand is Keithley, and the model is 2400. The commercial electroluminescent chip brand used in the present invention is Sanan Optoelectronics, the size is 5mm, and the emission peak position is 382nm. The instrument brand used to test the electroluminescent fluorescence signal is HORIBA, and the instrument model is Fluoro Max Plus.
[0128] Table 1
[0129]
[0130]
[0131] Figure 1 The fluorescence test results of the original MoS2 nanosheet dispersion and the passivated MoS2 nanosheet dispersion provided in Example 1 and Comparative Example 1 are compared, wherein the excitation wavelength is 380 nm. Figure 1 As shown, the fluorescence emission peak of the passivated MoS2 nanosheet of Example 1 is at 471nm, and the fluorescence emission peak of the original MoS2 nanosheet of Comparative Example 1 is at 488nm. Compared with Comparative Example 1, after the passivation method of the present invention and passivation by tetrahydrofuran, the fluorescence intensity of the passivated nanosheet of Example 1 is increased by 45 times, and the fluorescence intensity is significantly enhanced.
[0132] Figure 2 The fluorescence test results of the original MoS2 nanosheet dispersion and the MoS2 nanosheet dispersion provided in Example 2 and Comparative Example 2 are compared, wherein the excitation wavelength is 380 nm. Figure 2 As shown, compared with Comparative Example 2, after the passivation method of the present invention and passivation by tetrahydrofuran, the fluorescence intensity of the passivated nanosheets in Example 2 is increased by 13 times, and the fluorescence intensity is significantly enhanced.
[0133] Figure 3 The fluorescence test results of the original MoS2 nanosheet dispersion and the passivated MoS2 nanosheet dispersion provided in Example 3 and Comparative Example 3 are compared, wherein the excitation wavelength is 380nm. Figure 3 As shown, compared with Comparative Example 3, after the passivation method of the present invention and tetrahydrofuran passivation, the fluorescence intensity of the passivated nanosheets in Example 3 is increased by 5 times, and the fluorescence intensity is significantly enhanced.
[0134] Figure 4 The fluorescence test results of the original WS2 nanosheet dispersion and the passivated WS2 nanosheet dispersion provided in Example 4 and Comparative Example 4 are compared, wherein the excitation wavelength is 380 nm. Figure 4 As shown, the fluorescence emission peak of the passivated WS2 nanosheet of Example 4 is at 461nm, and the fluorescence emission peak of the original WS2 nanosheet of Comparative Example 4 is at 467nm. Compared with Comparative Example 4, after the passivation method of the present invention and passivation by tetrahydrofuran, the fluorescence intensity of the passivated nanosheet of Example 4 is increased by 103 times, and the fluorescence intensity is significantly enhanced.
[0135] Figure 5The fluorescence test results of the original MoSe2 nanosheet dispersion and the passivated MoSe2 nanosheet dispersion provided in Example 5 and Comparative Example 5 are compared, wherein the excitation wavelength is 380 nm. Figure 5 As shown, the fluorescence emission peak of the passivated MoSe2 nanosheet of Example 5 is at 448nm, and the fluorescence emission peak of the original MoSe2 nanosheet of Comparative Example 5 is at 457nm. Compared with Comparative Example 5, after the passivation method of the present invention, the fluorescence intensity of the passivated nanosheet of Example 5 is increased by 85 times after passivation by diethyl sulfide, and the fluorescence intensity is significantly enhanced.
[0136] Figure 6 The fluorescence test results of the original Bi2Se3 nanosheet dispersion and the passivated Bi2Se3 nanosheet dispersion provided in Example 6 and Comparative Example 6 are compared, wherein the excitation wavelength is 380nm. Figure 6 As shown, the fluorescence emission peak of the passivated Bi2Se3 nanosheet of Example 6 is at 459nm, and the fluorescence emission peak of the original Bi2Se3 nanosheet of Comparative Example 6 is at 462nm. Compared with Comparative Example 6, after the passivation method of the present invention, the fluorescence intensity of the passivated nanosheet of Example 6 is increased by 48 times after passivation by ether, and the fluorescence intensity is significantly enhanced.
[0137] Figure 7 The fluorescence test results of the original MoS2 nanosheet dispersion and the passivated MoS2 nanosheet dispersion provided in Example 7 and Comparative Example 7 are compared, wherein the excitation wavelength is 380 nm. Figure 7 As shown, compared with comparative example 7, after passivation by N-methylpyrrolidone using the passivation method of the present invention, the fluorescence intensity of the passivated nanosheets of example 7 is increased by 14 times, and the fluorescence intensity is significantly enhanced.
[0138] Figure 8 The fluorescence test results of the passivated MoS2 nanosheet dispersion provided in Example 1 after 20 days, 40 days, and 60 days, wherein the excitation wavelength is 380nm. Figure 8 As shown, under 380nm excitation, the fluorescence intensity of the passivated MoS2 nanosheets of Example 1 decreased by 2.5% after 20 days at room temperature compared with 0 days, decreased by 2.8% after 40 days at room temperature compared with 0 days, and decreased by 2.9% after 60 days at room temperature compared with 0 days. The passivated nanosheets maintained good fluorescence stability.
[0139] Fig. 9 The electroluminescence results of the passivated WS2 nanosheets provided in Application Example 1 coated on a commercial electroluminescent chip as a fluorescent conversion material, wherein the driving current is 10 mA and the electroluminescence peaks are at 409 nm and 540 nm.
[0140] Fig.10 The electroluminescence results of the unpassivated WS2 nanosheets coated on a commercial electroluminescent chip provided in Comparative Application Example 1, wherein the driving current is 10 mA and the electroluminescence peak is at 380 nm.
[0141] Compared with comparative application example 1, the emission peak of the electroluminescent chip using passivated WS2 nanosheets as the fluorescence conversion material in application example 1 is significantly changed, and the fluorescence conversion effect is significant.
[0142] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A passivation method for passivating transition metal dichalcogenide nanosheets, characterized in that: The passivation method comprises the following steps: (1) dispersing transition metal dichalcogenide nanosheets in a passivation agent, and subjecting the dispersion to a first ultrasonic treatment to obtain an original dispersion of transition metal dichalcogenide nanosheets; (2) heating the original dispersion of transition metal dichalcogenide nanosheets in step (1) to obtain the passivated transition metal dichalcogenide nanosheets.
2. The passivation method according to claim 1, characterized in that: The transition metal dichalcogenide nanosheets in step (1) include any one of MoS2, MoSe2, WS2, WSe2, Bi2Se3, InS2 or InSe2, or a combination of at least two thereof; Preferably, the lateral size of the transition metal dichalcogenide nanosheet in step (1) is less than 100 nm, preferably 2 nm-10 nm; Preferably, the thickness of the transition metal dichalcogenide nanosheet in step (1) is less than 3 nm, preferably 0.6 nm-2 nm.
3. The passivation method according to any one of claims 1 to 2, characterized in that: The passivation reagent in step (1) comprises any one of tetrahydrofuran, N-methylpyrrolidone, ether or diethyl sulfide, or a combination of at least two thereof, preferably tetrahydrofuran; Preferably, the mass concentration of the transition metal dichalcogenide nanosheets in the original dispersion of the transition metal dichalcogenide nanosheets in step (1) is 0.005 mg / mL-0.2 mg / mL, preferably 0.02 mg / mL-0.1 mg / mL.
4. The passivation method according to any one of claims 1 to 3, characterized in that: Step (1) The power of the first ultrasonic treatment is 50W-800W, preferably 100W-200W; Preferably, the time of the first ultrasonic treatment in step (1) is 1 min to 100 min, preferably 10 min to 30 min; Preferably, the first ultrasonic treatment method in step (1) comprises probe ultrasonication or water bath ultrasonication.
5. The passivation method according to any one of claims 1 to 4, characterized in that: The passivation method in step (1) further comprises standing after the first ultrasonic treatment is completed; Preferably, the standing temperature is 0°C-40°C, preferably 15°C-25°C; Preferably, the standing time is 0.2h-5h, preferably 0.2h-1h.
6. The passivation method according to any one of claims 1 to 5, characterized in that: The temperature of the heating treatment in step (2) is 100°C-200°C, preferably 100°C-120°C; Preferably, the heating treatment time in step (2) is 10 min-400 min, preferably 230 min-250 min; Preferably, after the heating treatment in step (2) is completed, the mixture is allowed to stand and cool to 0°C-40°C; Preferably, the cooling time is 10 min-30 min.
7. The passivation method according to any one of claims 1 to 6, characterized in that: The passivation method also includes a redispersion process after standing and cooling; Preferably, the redispersion process comprises dispersing the passivated transition metal disulfide compound nanosheets in a dispersing agent to obtain a passivated transition metal disulfide compound nanosheet dispersion; Preferably, the dispersing agent includes any one or a combination of at least two of N-methylpyrrolidone, N-vinylpyrrolidone, N-cyclohexylpyrrolidone, N-octylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran, acetone, ether, diethyl sulfide, methanol, ethanol, toluene, isopropanol or water; Preferably, the mass concentration of the passivated transition metal dichalcogenide nanosheets in the passivated transition metal dichalcogenide nanosheet dispersion is 0.001 mg / mL-10.0 mg / mL, preferably 0.02 mg / mL-0.1 mg / mL; Preferably, the method of the redispersion process comprises a second ultrasonic treatment; Preferably, the ultrasonic power of the second ultrasonic treatment is 100W-200W; Preferably, the ultrasonic time of the second ultrasonic treatment is 5 min-60 min.
8. A passivated transition metal dichalcogenide nanosheet, characterized in that: The passivated transition metal dichalcogenide nanosheets are prepared by the passivation method according to any one of claims 1 to 7.
9. The passivated transition metal dichalcogenide nanosheet according to claim 8, characterized in that: The thickness of the passivated transition metal dichalcogenide nanosheet is less than 3 nm, preferably 0.6 nm to 2 nm; Preferably, the lateral size of the passivated transition metal dichalcogenide nanosheet is less than 100 nm, preferably 2 nm-10 nm.
10. Use of the passivated transition metal dichalcogenide nanosheet according to claim 8 or 9, characterized in that: The passivated transition metal dichalcogenide nanosheet is applied to optoelectronic devices, optical films, biosensors, fluorescent indicators or fluorescent conversion materials.
Citation Information
Patent Citations
Surface passivated CdTe nanocrystalline film and surface passivation treatment method and application thereof
CN110098331A
Solid-state photoinduced fluorescence enhancement material, preparation method and application of solid-state photoinduced fluorescence enhancement material
CN117534606A
Method for passivating surface of quantum dot and application thereof
CN118325612A